Phylogeography and Population Genetics of Rosa chinensis var. spontanea and R. lucidissima Complex, the Important Ancestor of Modern Roses - Jian, Hongying; Zhao, Ling; Zhang, Hao; Ma, Changle; Wang, Qigang; Yan, Huijun; Qiu, Xianqin; Zhou, Ningning; Zhang, Ting (Frontiers in Plant Science, 2022)
Rosa chinensis var. spontanea and R. lucidissima complex are the morphologically very similar key ancestors of modern roses with high importance in rose research and breeding. Although widely distributed in subtropical central and southwestern China, these two taxa are highly endangered. We sampled a total of 221 specimens and 330 DNA samples from 25 populations across the two taxa's whole range. Leaf morphological traits were compared. Two chloroplast DNA intergenic spacers (trnG-trnS, petL-psbE) and ITS were used for population genetics and phylogenetic study to delimit the boundary between the two taxa, assess the genetic variation, uncover the possible evolutionary mechanism responsible for the differentiation within the complex, and make the conservation recommendations. The complex exhibited high levels of genetic variation (hTcpDNA = 0.768, hTITS = 0.726) and high population differentiation even over small geographic distance. We suggest R. chinensis var. spontanea and R. lucidissma be treated as independent taxa, and the northern populations around and within the Sichuan Basin being R. chinensis var. spontanea, having broader leaflets and paler full-blooming flowers, while those in the middle and southern Yunnan-Guizhou Plateau and the adjacent regions being R. lucidissma, having narrower leaflets and darker full-blooming flowers. Transitional areas between the southeastern Sichuan Basin and northeastern Guizhou are the contact or the hybridization zone of the two taxa. Ancestral haplotypes of the complex (R. lucidissma) evolved at about 1.21–0.86 Mya in southeastern Yunnan-Guizhou Plateau and its adjacent regions and survived there during the Quaternary Oscillation. Ancestral haplotypes of R. chinensis var. spontanea deviated from R. lucidissma at about 0.022–0.031 Mya at the transitional areas (Daloushan and Wulingshan Mountains) between the northeastern edge of Yunnan-Guizhou Plaeteau and the southeastern border of Sichuan Basin, where they survived the LGM. The evolution of the complex included spatial isolation and inter-species hybridization. The complex's endangered status might be the result of over-exploitation for its ornamental and medical value, or due to reforestation of some originally open habitats. We provide specific recommendations for the two taxa's in situ and ex situ conservation.